Chemical Composition of Essential Oils from Bark and Leaves of Pinus brutia Ten. from Turkey - Bagci, Eyup; Hayta, Sukru; Dogan, Gulden (Asian Journal of Chemistry, 2011)
The chemical composition of essential oils obtained by hydrodistillation of leaves and bark of Pinus brutia was investigated by GC and GC-MS. The essential oil content was 0.8 % (v/w), 0.7 % (v/w), respectively. In the leaf oil of Pinus brutia, beta-pinene (29.5 %), germacrene D (17.9 %), alpha-pinene (14.4 %), beta-caryophyllene (9.8 %) were the main constituents. In the bark oil Pinus brutia, a-pinene (14.9 %), beta-caryophyllene (11.2 %), delta-3-carene (9.6 %), caryophyllene oxide (6.9 %) as the major constituents. A total of 95 compounds have been identified constituting 86.3 % bark, 94.1 % leaves in the essential oils.
Keywords: Pinus brutia; GC-MS; Essential oil; alpha-Pinene; Leaf; Bark